2021
DOI: 10.1002/ehf2.13468
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial factors, mental health, and coordination capacity in patients with heart failure with preserved ejection fraction compared with heart failure with reduced ejection fraction

Abstract: Aims Patients with heart failure (HF) suffer from reduced quality-of-life (QoL). We aimed to compare QoL, depression, and anxiety scores among outpatients with preserved (HFpEF) and reduced (HFrEF) ejection fraction and non-HF controls and its relationship to coordination capacity. Methods and results Fifty-five participants were recruited prospectively at the University Hospital Jena, Germany (17 HFpEF, 18 HFrEF, and 20 non-HF controls). All participants underwent echocardiography, cardiopulmonary exercise te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Haider et al [ 26 ] reported that in patients aged above 60 years with heart failure, the probability of depressive disorder was significantly higher in patients with LVEF >45% than in those with LVEF <45%. Tarek et al [ 27 ] found that patients with heart failure with preserved LVEF had significantly more severe depressive disorder than those with heart failure with reduced LVEF. However, some studies have found inconsistent conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Haider et al [ 26 ] reported that in patients aged above 60 years with heart failure, the probability of depressive disorder was significantly higher in patients with LVEF >45% than in those with LVEF <45%. Tarek et al [ 27 ] found that patients with heart failure with preserved LVEF had significantly more severe depressive disorder than those with heart failure with reduced LVEF. However, some studies have found inconsistent conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…The cardinal symptoms of heart failure are breathlessness, fatigue, and ankle swelling (McDonagh et al, 2021). These symptoms are responsible for impairing physical activity, as well as the aspects of patients' mental and social life (Bekfani et al, 2021). As coping with the symptoms may be challenging, the emotional and physical well-being of these patients is quite poor (Park and Lee, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…As coping with the symptoms may be challenging, the emotional and physical well-being of these patients is quite poor (Park and Lee, 2020). Therefore, it is not uncommon to observe a relatively high prevalence of depression (Rutledge et al, 2006) and other mental disorders independently associated with more deaths and hospital readmissions (Bekfani et al, 2021;Sokoreli et al, 2018). Although the association between depression and heart failure has long been known, depression is still underrecognized and thus undertreated (Sbolli et al, 2020), despite the fact that it is listed among the comorbidities of heart failure in the European Society of Cardiology (ESC) guidelines for the diagnosis and treatment of acute and chronic heart failure (McDonagh et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“… 9 Moreover, QoL of HFpEF patients may be massively restricted and associated with psychological distress, anxiety, and depression. 10 By identifying predictors of future QoL, one might be able to treat those and improve patient's overall QoL early in the disease process. 11 Several studies including patients with heart failure and reduced ejection fraction (HFrEF) or mixed collectives of HF patients found, that QoL is, amongst others, influenced by physical and psychological symptoms, age, sex, and New York Heart Association (NYHA) class.…”
Section: Introductionmentioning
confidence: 99%
“…Even under optimal therapy, patients suffer from progressive symptoms and die prematurely 9 . Moreover, QoL of HFpEF patients may be massively restricted and associated with psychological distress, anxiety, and depression 10 . By identifying predictors of future QoL, one might be able to treat those and improve patient's overall QoL early in the disease process 11 .…”
Section: Introductionmentioning
confidence: 99%